Source apportionment of water pollutants in Poyang Lake Basin in China using absolute principal component score–multiple linear regression model combined with land-use parameters - Hou, Xikang; Gao, Wei; Zhang, Meng; Xia, Rui; Zhang, Yuan; Zhang, Kai; Wang, Xiao; Yang, Kai; Chen, Xiaofei; Deng, Yu (Frontiers in Environmental Science, 2022)
Accurate identification of potential contamination sources of surface water is a basis for effective pollution control and sustainable water management. Mechanistic models usually require so much data and so many parameters for calibration, making their application difficult for complex hydrologic condition watershed. However, reverse source tracing methods based on hydrochemistry-parameters-only method may lead to uncertainty and subjectivity. In this study along with hydrochemistry parameters, land use were considered as an auxiliary in principal component analysis (PCA) to achieve a comprehensive assessment on pollution sources with accurate estimates of source identification and apportionment. Thirteen hydrochemistry parameters were combined with two meteorology parameters in multivariate statistics to quantitatively assess potential pollution sources and their contributions to surface water pollution of Poyang Lake Basin, which frequent flow and sediment flux exchange with Yangtze River make the river-lake relationship complex. PCA methods were applied to identify five potential pollution sources. Absolute principal component score-multiple linear regression (APCS-MLR) model was used to apportion their contributions to each water quality variable. Results showed that urban waste water with 34% contribution and agricultural non-point sources with 16% contribution, were the major sources of pollution in water quality. To TP and NH3-N, the most serious pollutions, agricultural non-point source pollutions with 40% contributions and urban waste water with 21% contributions was the major sources in Poyang Lake Basin. Urban waste water with 60% contributions was the major source of organic contamination. It can be concluded that urban domestic sewage, industrial effluents and agricultural non-point source were the major sources of water contamination in Poyang Lake Basin.